AL-SUYŪṬĪ WA ITTIJᾹHᾹTUH ILᾹ AL-TAFSĪR AL-‘ILMĪ DIRᾹSAH ‘ALᾹ TAFSĪR ᾹYᾹT AL-WABᾹ - Zaeni, Ahmad; Muiz, Abdul; Hajar, Siti (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2021)
This article discusses the tendency of Tafsīr 'Ilmī in Imam Suyuti's interpretation of the plague verses. Interestingly, as a classical commentator, he interprets the plague verses in his commentary books using the traditions of the Prophet (naqli), but he explains about the plague in addition to his commentary books by referring to the interpretation of the plague verses which are supported by scientific data. To analyze the tendency of this interpretation (ittijāh al-tafsīr), the researcher uses the theory of scientific interpretation. This research is qualitative in nature and uses content analysis methods, especially the istiqra (inductive) method. The istiqra method is used to analyze his interpretation of the plague verses that are spread in his commentaries and his books on epidemics and medicine. The purpose of this study is to reveal the indications of the trend of scientific interpretation explored by Imam Suyūtī in his books on epidemics and medicine by referring to his interpretations in his commentary books, so this research is urgent to confirm the historical roots and dynamics of Tafsīr 'Ilmī, whose epistemological tendency has emerged in the era of classical scholars. The results of this study are, first, in general, the method of interpretation of Imam Suyūtī is bi al-ma'ṣūr. Second, Imam Suyūtī's interpretation of the plague verses in Ṭā'ūn and medical themed books tends to 'Ilmi' Tafsir in terms of a more scientific explanation of the narrations that are in accordance with science, medical and socio-historical. Third, the scientific tendency in Imam Suyūtī's interpretation is in historical and medical.